2016
DOI: 10.1590/1808-1657000222015
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Selenisa sueroides (Guenée, 1852) (Lepidoptera: Noctuidae) in soybeans in Brazil

Abstract: In this study, we report the occurrence of Selenisa sueroides (Guenée, 1852) in soybean crops in Brazil. S. sueroides worms were observed defoliating soybean crops in the municipality of Itaporã, state of Mato Grosso do Sul. The occurrence of this species has also been reported in the cities of Laguna Carapã, Itaquiraí, Dourados, Aral Moreira, and Chapadão do Sul, all in the same state, and the municipality of Campo Novo do Parecis, in Mato Grosso state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…detected the insect species in vines in Bento Gonçalves, also in Rio Grande do Sul. Last year, in 2016, there were also records of S. sueroides larvae attacking soybean fields in several counties of the Mato Grosso do Sul state(sANtOs et al 2016). After field-collecting developed larvae of S. sueroides in soybeans, sANtOs et al (2016) observed pupae duration of 15 days and adult longevity of 16-18 days; however, these authors could not evaluate the reproductive parameters due to the low number of surviving adults.…”
mentioning
confidence: 99%
“…detected the insect species in vines in Bento Gonçalves, also in Rio Grande do Sul. Last year, in 2016, there were also records of S. sueroides larvae attacking soybean fields in several counties of the Mato Grosso do Sul state(sANtOs et al 2016). After field-collecting developed larvae of S. sueroides in soybeans, sANtOs et al (2016) observed pupae duration of 15 days and adult longevity of 16-18 days; however, these authors could not evaluate the reproductive parameters due to the low number of surviving adults.…”
mentioning
confidence: 99%